Unveiling the functional diversity of ionotropic glutamate receptors in the Pacific oyster (Crassostrea gigas) by systematic studies - Zhang, Xueshu; Zhang, Linfang; Si, Yiran; Wen, Xue; Wang, Lingling; Song, Linsheng (Frontiers in Physiology, 2023)
Abstract Ionotropic glutamate receptors (iGluRs), central to the mediation of most excitatory neuro signals within the central nervous system, also play a significant role in environmental stress responses. In the present study, 12 iGluRs were identified and characterized in the Pacific oyster, termed CgiGluRs, which were further divided into three distinct subfamilies, each exhibiting a transmembrane domain. An evolutionary analysis across species revealed a high degree of conservation in the sequence and structural attributes of these CgiGluRs. These receptors are ubiquitously distributed across various tissues, with pronounced expression in the mantle, labial palps, and gills of oyster, highlighting their integral role in the oyster's environmental sensing mechanisms. From the D-shaped larval stage onward, the expression of CgiGluRs demonstrated an upward trend, indicating their crucial involvement in the development of the oyster beyond this stage. Upon exposure to five metals – cadmium (Cd), copper (Cu), zinc (Zn), mercury (Hg), and lead (Pb) – a significant upregulation of CgGRIA4 expression was observed, signaling a robust response to metal stress. KEGG enrichment analysis was conducted on 142 genes that exhibited similar expression trends as CgGRIA4 under metal stress. The results suggested that CgGRIA4 could potentiate excitatory signal transmission by activating glutamatergic and dopaminergic synapses, thereby contributing to the metal stress response in the oyster. This investigation not only enhances our understanding of the role of the iGluRs gene family in metal stress response, but also lays the groundwork for future exploration of its crucial role in cellular signaling and environmental adaptability.